2021
DOI: 10.1111/iju.14738
|View full text |Cite
|
Sign up to set email alerts
|

Impact of neoadjuvant androgen deprivation therapy on postimplant prostate D90 and prostate volume after low‐dose‐rate brachytherapy for localized prostate cancer

Abstract: Objective Higher quality of postimplant dosimetric evaluation is associated with higher biochemical recurrence‐free survival rates after low‐dose‐rate brachytherapy for localized prostate cancer. Postimplant prostate D90 is a key dosimetric parameter showing the quality of low‐dose‐rate brachytherapy. In this study, to improve the quality of low‐dose‐rate brachytherapy for localized prostate cancer, we investigated pre‐implant factors affecting the reduction of postimplant prostate D90. Methods A total of 441 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 31 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…We have previously reported the oncologic outcomes of LDR‐BT several times 7–9 . In the present study, we updated the oncologic outcomes with a longer follow‐up period.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…We have previously reported the oncologic outcomes of LDR‐BT several times 7–9 . In the present study, we updated the oncologic outcomes with a longer follow‐up period.…”
Section: Discussionmentioning
confidence: 91%
“…We have previously reported the oncologic outcomes of LDR-BT several times. [7][8][9] In the present study, we updated the oncologic outcomes with a longer follow-up period. Stone et al reported 7-year biochemical freedom from failure of 91.6%, 83.9%, and 70.3% in the low-, intermediate-, and high risk groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations